ЗВ’ЯЗОК МІЖ ПОКАЗНИКАМИ ТІЛОБУДОВИ І МІНЕРАЛЬНОЇ ЩІЛЬНОСТІ КІСТКОВОЇ ТКАНИНИ У ПРАКТИЧНО ЗДОРОВИХ ЧОЛОВІКІВ ТА ПАЦІЄНТІВ ІЗ ТРАВМОЮ ХРЕБТА Й СПИННОГО МОЗКУ (World Science, 2018)
The purpose of the study was evaluating the peculiarity of bone mineral density (BMD) and body composition in patients with spinal cord injury (SCI). 51 men with SCI were enrolled to the study. The comparison group consists of 51 healthy men which were standardized by age and body weight. The study revealed in patients with SCI significantly higher rate of osteoporosis (84.31%) and sarcopenia (43.14%) in comparison with healthy men (1.96% and 25.49% accordingly). In healthy men the correlation analysis revealed the wide-ranging influence of body composition on lower extremities BMD. Thus, femur neck BMD is determined by the lean mass of upper extremities (r = 0.33, p